STUDENT ENGAGEMENT DURING ENGLISH LEARNING ACTIVITIES BY USING SONG FOR ENGLISH YOUNG LEARNER AT SDN 01 TARATAK - Miski, Cut Raudhatul; Ramadhani, Allya; Kurniawati, Dinda; Efrinalda, Dita; Muflih, Muhammad Naufal Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student engagement is an important factor in achieving effective English learning outcomes, particularly for young learners. However, maintaining students’ attention and active participation in the classroom remains a challenge due to their limited attention span and varying levels of interest. One instructional strategy that can enhance engagement is the use of songs. This study aimed to describe student engagement during English learning activities by using songs for young learners at SDN 01 Taratak. The study employed a quantitative descriptive design involving 16 fifth-grade students as participants. Data were collected through an observation checklist adapted from Fredricks et al. (2004), which measured three dimensions of student engagement: behavioral, cognitive, and emotional engagement. The data were analyzed using descriptive statistics, including mean scores, percentages, and engagement categories. The findings revealed that students demonstrated a high level of engagement during song-based English learning activities. Behavioral engagement obtained a mean score of 18.00 and was categorized as very high, indicating active participation in classroom activities. Cognitive engagement obtained a mean score of 14.50 and was categorized as high, showing that students paid attention and attempted to understand the learning materials. Emotional engagement obtained a mean score of 18.00 and was categorized as very high, reflecting students’ enthusiasm and enjoyment during the lessons. The overall mean engagement score was 50.50, which indicates a very high level of student engagement. These findings suggest that songs can effectively promote behavioral, cognitive, and emotional engagement among young learners. Therefore, incorporating songs into English learning activities can create a more interactive, enjoyable, and engaging classroom environment.